Comparison between face-to-face bullying and cyber-bullying amongst elementary school students and how they cope - Stefán Örn Guðmundsson 1982- (2013)
Face-to-face bullying has been described as aggression from two or more students against a student repeatedly and over time (Olweus, 1996). The increasing availability of internet and an extensive technology development in cell phones has given adolescents a new way to bully. Cyber-bullying is a new form of bullying and can damage adolescents’ social and emotional development (Raskauskas & Stoltz, 2007). The main focus of the current study was to examine the relationship between face-to-face bullying and cyber-bullying and whether cyber-bullying has a similar influence on adolescent feelings as face-to-face bullying. The present study used archival data, Youth in Iceland 2011. Participants were elementary students in Iceland. The sample size was 2,000 and there were 982 boys and 996 girls in the study (22 participants did not register their sex). The questionnaire was administered to students in all middle schools in Iceland. The hypothesis was that face-to-face bullying and cyber-bullying would have similar emotional impact on elementary school students. Results from multiple hierarchal regression models (controlling for gender, age, and family structure) revealed that face-to-face bullying and cyber-bullying were significantly related to bad feelings, feeling unsafe, quitting school and social isolation. These results indicate that face-to-face bullying and cyber-bullying might be risk factors for bad emotional impacts on elementary school students. Hefðbundið einelti hefur verið skilgreint sem árásargirni frá tveimur eða fleiri nemendum gagnvart einum nemanda sem á sér stað ítrekað í langan tíma (Olweus, 1996). Tilkoma aukinnar netnotkunar og hröð tækniþróun í farsímum hefur opnað unglingum fleiri leiðir til þess að leggja einhvern í einelti. Einelti á netinu er ný útgáfa af einelti og getur skaðað félagslegan og tilfinningalegan þroska unglinga (Raskauskas & Stoltz, 2007). Tilgangur rannsóknarinnar var að rannsaka tengslin á milli hefðbundins eineltis og eineltis á netinu og kanna hvort einelti á ...